SIFAT-SIFAT DAN KEJADIAN KHUSUS DISTRIBUSI GAMMA - Warella, Royke Yohanes; Wattimanela, Henry Junus; Ilwaru, Venn Yan Ishak (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
The gamma distribution is one of special continuous random variable distribution with scale parameter and shape parameter where is positive real numbers. On some conditions the gamma distribution astablishes other continuous distributions which are then called special cases of the gamma distribution. Therefore, this study was conducted to determine the properties of gamma distribution and the characteristics of the special cases of gamma distribution by analyzed the theories from literatures. The properties of gamma distribution include expectation value, variance, moment generating function, characteristic function, and estimation of gamma distribution parameters with the moment method to earn the special cases of the gamma distribution are Erlang, exponential, chi-square, and beta distributions.